(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: The increasing demand for having an attractive smile becomes one of the life essentials. Oral hygiene maintenance plays a key role in maintaining oral health (healthy teeth and gum) and as a result, having an attractive smile. Thus, using routine dental cleansing through brushing, flossing and mouth rinsesis mandatory. This study aims to evaluate the role played by social media on consumers’ behaviour to use dental products manufactured essentially from herbal products rather than the well- known chemical formula. The analyzed data were collected by using a face-to-face approach (unstructured interviews). At first, dentists and pharmacists were asked about their opinion regarding using herbal products and their response to social media campaigns. Then,a random sample of the audience was interviewed. Results showed that most of the Iraqi peoples are familiar with herbal products (68.6 %)of them indicated social media has an impact on individuals. The awareness of the importance of using toothpaste and mouth rinses made from herbal products can be increased through introducing their effectiveness, reduced side effect and their importance as green substrates…etc. This can be done by organized campaigns by a pharmaceutical company or nonprofit organization.